Assembly, annotation, and comparative whole genome sequence of fusarium verticillioides isolated from stored maize grains - Navale, Vishwambar D.; Sawant, Amol M.; Gowda, Varun U.; Vamkudoth, Koteswara Rao (2022)
Fusarium verticillioides is a plant pathogenic fungus affecting a wide range of crops worldwide due to its toxigenic properties. F. verticillioides BIONCL4 strain was isolated from stored maize grain samples in India, and produces high amount of fumonisin B1 (FB1). We report a comparative genomic analysis of F. verticillioides, covering the basic genome information, secretome, and proteins involved in host-pathogen interactions and mycotoxin biosynthesis. Whole-genome sequencing (WGS) was performed using the Illumina platform with an assembly size of 42.91 Mb, GC content of 48.24%, and 98.50% coverage with the reference genome (GCA000149555). It encodes 15,053 proteins, including 2058 secretory proteins, 676 classical secretory proteins, and 569 virulence and pathogenicity-related proteins. There were also 1447 genes linked to carbohydrate active enzymes (CaZymes) and 167 genes related to mycotoxin production. Furthermore, F. verticillioides genome comparison revealed information about the species' evolutionary history. The overall study helps in disease prevention and management of mycotoxins to ensure food safety.
Keywords: comparative genomics; Fusarium verticillioides; mycotoxin biosynthesis; plant-pathogen interaction; Secretome; whole-genome sequencing

Expanding the Egbenema horizon: Novel species discovery in India and first complete genome assembly of the genus - Bhagat, Jayesh M.; Khilari, Ajinkya A.; Shanmugam, Dhanasekaran; Patankar, Meena (Algal Research-Biomass Biofuels and Bioproducts, 2025)
The recognition of Egbenema bharatensis, a novel species of cyanobacteria from the Northern Western Ghats, extends the ecological and phylogenetic understanding of the genus Egbenema and highlights terrestrial microbial diversity of the region. Morphological characterization revealed resemblance with other Egbenema species but was inconclusive for definitive taxonomic classification. Preliminary phylogenetic analysis based on 16S rRNA gene sequences indicated affiliation with the genus but showed less than 98 % similarity to known species, pointing toward taxonomic distinctiveness. Analysis of the 16S-ITS region further supported this differentiation, revealing unique secondary structural features. Based on these findings, we propose the isolate as a novel species within Egbenema. Whole-genome sequencing provided full resolution and functional genome annotation revealed nitrogen fixation, cobalamin biosynthesis, and stress tolerance pathways, suggesting its metabolic versatility and potential biotechnological applications. The presence of multiple toxin-antitoxin systems also reflects its adaptability to environmental fluctuation. This study also presents the first complete genome of the genus Egbenema, filling a significant gap in cyanobacterial genomic resources. These findings encourage integrative taxonomic practices and affirm the significance of exploring biodiversity hotspots for uncovering cryptic microbial diversity with ecological and industrial potential.
Keywords: 16S rRNA; Biodiversity hotspots; Cyanobacteria; Egbenema bharatensis; ITS secondary structure; Northern Western Ghats; whole-genome sequencing